SISTEM DETEKSI DAN PEMROSESAN SINYAL ABSORPSI SPEKTROSKOPI UNTUK PENSTABILAN FREKUENSI LASER YANG DISIMULASIKAN SECARA ELEKTRONIK - Chusno Trijanto, Anang
Detection and processing system of spectroscopy absorption signal for electronic simulated laser frequency stabilization Laser frequency stabilization with absorption line reference needs a high signal to noise ratio (S/N) line frequency absorption detection system. For these purposes, detection and processing system of spectroscopy absorption signal has been developed. The system identifies the peak of absorption curve by mean of scan around the curve. For study and analyzing purposes, Lorentzian model is implemented to off-line process. However, in frequency stabilization, parabolic model is implemented around the top of the curve. This is expected to improve the long-term stability of laser frequency control system, by decreasing Allan Standard Deviation, ay.(t), at i z, 100 s up to 1000 s or more. This method is then applied on a 12 MHz electronic absorption simulator. The test result demonstrates that Lorentzian approach has constraint due the difficulty of analytic evaluation for on-line implementation. While with parabolic approach these difficulties are not shown. The resulting deviation standard a = 1.26E-01 and a = 1. 39E-01. Its higher than, but relatively close to that of Lorentzian approach a = 1.05 E-01. In frequency stabilization, peak identification is then use as a basic data to produce correction signal that will shift the output frequency. Stability analyzing in time domain, show that Allan Standard Deviation, a(t), decreases at 100 s 5 T 5 1000 s but it increases at 1 s 5 t 5 20 s. It shows that S/N improvement occurs at 100 s 5. z 5 1000 s, that mean long-term stability is improved.